CHANGES IN THE LEVEL OF FoxP3+ REGULATORY T LYMPHOCYTES IN PATIENTS WITH EARLY RHEUMATOID ARTHRITIS DURING METHOTREXATE THERAPY - A. S. Avdeeva; Yu. P. Rubtsov; T. V. Popkova; D. T. Dyikanov; E. L. Nasonov (Научно-практическая ревматология)
Objective: to analyze the impact of methotrexate (MTX) therapy on percentage and absolute content of FoxP3+ regulatory T lymphocytes (Treg) in the peripheral blood of patients with early rheumatoid arthritis (RA) who had not previously received MTX.Subjects and methods. The investigation included 45 patients with early RA (2010 ACR/EULAR criteria) who had not previously received MTX, including 39 women; median age was 52.0 [32.5; 57.5] years; disease duration, 5 [4; 6] months, DAS28, 5.01 [4.18; 5.8]; 71.1% of the patients were positive for rheumatoid factor and 88.9% – for anticyclic citrullinated peptide antibodies. As the first disease-modifying antirheumatic drug, all the patients were assigned to receive subcutaneous MTX at an initial dose of 10 mg/week with its rapid escalation up to 20–25 mg/week. The percentage and absolute count of Treg (FoxP3+CD25+; CD152+surface; CD152+intracellular; FoxP3+CD127-; CD25+CD127-; FoxP3+ICOS+; FoxP3+CD154+; and FoxP3+CD274+) were measured by immunofluorescence staining and multicolor flow cytometry.Results and discussion. At 24 weeks after starting the therapy, median DAS28, SDAI, and CDAI were 3.1 [2.7; 3.62], 7.4 [4.2; 11.4], and 7.0 [4.0; 11.0], respectively; DAS28 and SDAI remission/low disease activity was reached by 22 (56.4%) and 25 (64.1%) patients, respectively; 4 (10.3%) patients had no MTX treatment effect according to the EULAR criteria. After a 6-month course of MTX therapy, the whole group had increases in the percentage of CD4+cells (from 45.0 [38.0; 49.2] to 46.8 [39.9; 53.2]%) and in the percentage and absolute number of CD152+surface from 0.65 [0.22; 1.67] to 2.07 [1.11; 3.81]% and from 0.0002 [0.0001; 0.0008]•109 to 0.0007 [0.0004; 0.002]•109, and a moderate decrease in the percentage and absolute content of FoxP3+ICOS+ cells from 5.3 [2.1; 11.3] to 4.07 [1.6;6.6]% and from 0.002 [0.001-0.006]•109 to 0.0015 [0.0006-0.003]•109 (p<0.05 in all cases).Conclusion. The use of MTX in early RA is accompanied by an increase in the proportion and number of Treg with a high level of activation markers, which may indicate their enhanced suppressor activity that is more pronounced among the patients who have achieved remission/low disease activity during the treatment.